Wormhole Models and Energy Conditions in fℛ Gravity with the Hu–Sawicki Model - Ouziala Ikram; G. Mustafa (Advances in Astronomy)
In this recent study, we shall investigate the wormhole models with a Hu–Sawicki model in the framework of fℛ gravity. Spherically static symmetric space-time is considered to construct wormhole models with the anisotropic fluid distribution. The traceless matter is discussed by imposing a particular equation of state. To address the important conditions of the shape function of the wormhole geometry, we have used the particular values of the involved parameters. Furthermore, different energy conditions are discussed to check the nature of matter against two specific models. The null energy condition is observed to be violated for both of the models. It is mentioned that our inquired results are acceptable.